KEEFEKTIVAN MEDIA TEKA-TEKI KARUTA UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA KELAS 1 SD - Salma, Lilik Royani; Wiratama, Novialita Angga (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Early reading ability is a crucial foundation in the development of children's literacy. However, in practice, first-grade students often face difficulties in recognizing letters, spelling, and understanding texts. To overcome these challenges, engaging and interactive learning media are needed. The Teka-Teki Karuta media was developed as an educational game-based learning tool that combines visual, motor, and cognitive elements. This study employed a quasi-experimental method with a pretest-posttest control group design. The research subjects were first-grade students at an elementary school in District Tuban, consisting of an experimental group and a control group. The results showed a significant improvement in the reading abilities of students who used the Teka-Teki Karuta media compared to those who were taught using conventional methods. Based on data analysis, the use of Teka-Teki Karuta media proved to be effective in improving the early reading skills of first-grade elementary students. Therefore, this media is recommended as a fun and alternative learning tool for early literacy development.